Development of water-soluble zein colloid particles and in situ antibacterial evaluation by multiple headspace extraction gas chromatography - Yan Yin; Fuzhen Zhou; Yechong Yin; Yonghong Peng (Food Science and Human Wellness)
In this work, water-soluble zein/sodium caseinate (SC) nanoparticles were prepared as a delivery system of antimicrobials through anti-solvent procedure. Two model antimicrobials (nisin and thymol) were coencapsulated into zein particles by different interaction. Release properties indicate that zein colloid particles can be used not only in neutral food but also in acidic foods. It is worth mention that the release of thymol was delayed simply by adding nisin. To investigate the antimicrobial properties of zein/SC particles, Escherichia coli and Bacillus subtilis, Listeria monocytogenes were selected as gram-negative and gram-positive indicator bacteria. CO2 produced by incubated germs was detected by headspace gas chromatography. Long-term effective antimicrobial activities of zein particles in Luria broth was attained by burst release of nisin and slowly sustained release of thymol. Synergistic antimicromibial properties against L. monocytogenes of thymol and nisin loaded by zein/SC particles in milk were also observed. The antimicrobial property of zein/SC particles could enhance microbial safety of food, giving this delivery system promising applications in food industry.